2013
DOI: 10.3109/13685538.2013.839648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of testosterone treatment on body composition in males with testosterone deficiency syndrome

Abstract: Testosterone treatment in males with TDS leads to body changes affecting lean and fat mass with significant improvement in AMS scores, and has an excellent safety profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 23 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…One possible explanation for the differences between our findings and those of Hildreth et al (22) may relate to the study duration (12 mo vs. 12 wk). Other studies reporting that T treatment alone decreases fat mass in men >50 yr compared with placebo have employed interventions for a minimum of 6 mo (51)(52)(53)(54)(55). Further supporting the notion that longer periods of combined T þ Ex administra-tion may be necessary to yield additive benefit for fat mass, Bhasin et al (21) did not report any changes in fat mass following a 10-wk intervention, despite using supraphysiological T dose.…”
Section: Discussionmentioning
confidence: 93%
“…One possible explanation for the differences between our findings and those of Hildreth et al (22) may relate to the study duration (12 mo vs. 12 wk). Other studies reporting that T treatment alone decreases fat mass in men >50 yr compared with placebo have employed interventions for a minimum of 6 mo (51)(52)(53)(54)(55). Further supporting the notion that longer periods of combined T þ Ex administra-tion may be necessary to yield additive benefit for fat mass, Bhasin et al (21) did not report any changes in fat mass following a 10-wk intervention, despite using supraphysiological T dose.…”
Section: Discussionmentioning
confidence: 93%
“…Rodrıguez-Tolra et al demonstrated clearly that TRT in men with TD decreased fat mass overall, and to the greatest extent in the android and gynecoid regions and caused improvements in body composition, increasing lean mass, primarily in arms and legs [ 83 ].…”
Section: Recommendation 6: Body Composition and Mobilitymentioning
confidence: 99%
“…A total of 84 studies that tested the effect of TRT on body composition met all our selection criteria. Forty-seven of these studies were RCTs ( (9,143,150,184,186,206,221,317). Two studies reported an increase in BMI (189,298).…”
Section: Scientific Literature On Trt Weight Bmi and Abdominal Obesmentioning
confidence: 99%